Hen's pens - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC, 2001)
When Hen runs out of paper she looks for other items on which to draw with her new pens.
"A phonics reader"--Cover.
Lift-the-flap pages.
2.5.
2.5
K-3
Keywords: Toy and movable books -- Specimens; Chickens -- Fiction; Stories in rhyme; Toy and movable books; Chickens -- Fiction; Stories in rhyme; Toy and movable books